A antropologia filosófica de Edgar Morin e suas contribuições para a filosofia da educação e para a prática do ensino em filosofia - Spirandeli Júnior, Antonio (2012)
This work presents the research results whose aim is the identification of the human conception present in Edgar Morin s work. Besides, its objective is also to analyze the possible contributions this conception may bring to educational practice, especially to the classes of Philosophy in the secondary school. We start from the comprehension the productions resulting of Edgar Morin s reflections on human being are a real philosophical anthropology. We have developed a bibliographical review, trying to understand philosophical anthropology, and also Edgar Morin s anthropological ideas. The following problems are the starting point: is it possible to say there is a philosophical anthropology present in Edgar Morin s complex thought theory? If so, what is the human being conception at play? What kind of contributions Edgar Morin s human being conception may offer to educational practice and, inside of it, to the teaching of Philosophy in the secondary school? The hypothesis we use as guidelines to this research are: Edgar Morin creates a philosophical anthropology bringing important contributions to this field of philosophical reflection. This complex philosophical anthropology can also offer contributions to the educational theory and to the Philosophy teaching in the secondary school. The research results are presented in three chapters named: Chapter I Philosophical Anthropology: conceptions and tendencies; Chapter II Edgar Morin s Complex Anthropology; Chapter III Complex Anthropology Contributions to Education. We shall find Conclusion after these chapters.